Urine Bisphenol-A Level in Relation to Obesity and Overweight in School-Age Children - Li, De-Kun (Public Library of Science, 2013)
Bisphenol-A (BPA) is a potential endocrine disruptor impacting metabolic processes and increasing the risk of obesity. To determine whether urine BPA level is associated with overweight/obesity in school-age children, we examined 1,326 students in grades 4–12 from three schools (one elementary, one middle, and one high school) in Shanghai. More than 98% of eligible students participated. Total urine BPA concentration was measured and anthropometric measures were taken by trained research staff. Information on risk factors for childhood obesity was collected for potential confounders. Age- and gender-specific weight greater than 90(th) percentile of the underlying population was the outcome measure. After adjustment for potential confounders, a higher urine BPA level (≥2 µg/L), at the level corresponding to the median urine BPA level in the U.S. population, was associated with more than two-fold increased risk of having weight >90(th) percentile among girls aged 9–12 (adjusted odds ratio (aOR) = 2.32, 95% confidence interval: 1.15–4.65). The association showed a dose-response relationship with increasing urine BPA level associated with further increased risk of overweight (p = 0.006 for trend test). Other anthropometric measures of obesity showed similar results. The same association was not observed among boys. This gender difference of BPA effect was consistent with findings from experimental studies and previous epidemiological studies. Our study suggests that BPA could be a potential new environmental obesogen. Widespread exposure to BPA in the human population may also be contributing to the worldwide obesity epidemic.